Management of patients with neck pain - E. A. Chechet; V. A. Parfenov (Неврология, нейропсихиатрия, психосоматика)
Neck pain (cervicalgia) occupies one of the leading places among the reasons for outpatient visits, 75% of people have experienced neck pain at least once in their lives. In most cases, neck pain regresses; however, it recurs in almost one half of patients. The paper gives data on the risk factors, mechanisms, course, and prognosis of cervicalgia. It discusses the issues of differential diagnosis, examination, and approaches to treating this condition in these patients. Nonsteroidal anti-inflammatory drugs are most effective in treating patients with acute cervicalgia. Therapeutic exercises and manual therapy are indicated in patients with chronic cervicalgia. There is evidence on the efficacy and safety of meloxicam for the management of acute and chronic cervicalgia.